Central hemodynamics changes in patients with coronary heart disease, stable effort angina, treated with mildronate - M. V. Baluda; V. V. Vikentyev; V. M. Fomina; N. Yu. Lavrenova; N. S. Baluda; I. V. Khvorostyanaya (Российский кардиологический журнал)
.